2005
DOI: 10.1098/rsbl.2005.0363
|View full text |Cite
|
Sign up to set email alerts
|

Shrimps remove ectoparasites from fishes in temperate waters

Abstract: We have found that two very common species of North Atlantic shallow water shrimp, Palaemon adspersus and Palaemon elegans, remove and feed on ectoparasites on plaice (Pleuronectes platessa L.). The relationship could be mutualistic, as we did not observe any attempts by the fishes to feed on the shrimps. The ectoparasites removed included monogenean worms (Gyrodactylus sp.) and sea lice (Lepeophtheirus pectoralis). An experiment showed that there were 65% more Gyrodactylus parasites on the fishes that had bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 8 publications
0
12
0
2
Order By: Relevance
“…If we were to consider the view of Spotte () to the exclusion of all observations of cleaning interactions in the literature, there would only be six shrimp considered as cleaners, notably Ancylomenes holthuisi (Palaemonidae) and Urocaridella sp. c. (Becker & Grutter, ), A. pedersoni (Bunkley‐Williams & Williams, ; McCammon et al ., ), Lysmata amboinensis (Militz & Hutson, ), and Palaemon adspersus (Palaemonidae) and Palaemon elegans (Palaemonidae) (Östlund‐Nilsson, Becker, & Nilsson, ). The view of Spotte () is probably premature.…”
Section: Consider the Grey Literature With Cautionmentioning
confidence: 99%
See 1 more Smart Citation
“…If we were to consider the view of Spotte () to the exclusion of all observations of cleaning interactions in the literature, there would only be six shrimp considered as cleaners, notably Ancylomenes holthuisi (Palaemonidae) and Urocaridella sp. c. (Becker & Grutter, ), A. pedersoni (Bunkley‐Williams & Williams, ; McCammon et al ., ), Lysmata amboinensis (Militz & Hutson, ), and Palaemon adspersus (Palaemonidae) and Palaemon elegans (Palaemonidae) (Östlund‐Nilsson, Becker, & Nilsson, ). The view of Spotte () is probably premature.…”
Section: Consider the Grey Literature With Cautionmentioning
confidence: 99%
“…Cleaner shrimp vary considerably in size between species and genera. Their size may influence the ability to remove and consume certain ectoparasites, for which they use their chelae (Karplus, ; Östlund‐Nilsson et al ., ; Yaldwyn, ), but small size also facilitates access into areas of the mouth and gill chamber of client fishes (Karplus, ). An increase in the robustness of the mandibles, as well as the morphological intricacy of the gastric mill reflects a carnivorous feeding habit in crustaceans (Kunze & Anderson, ).…”
Section: Morphology Colour and Behaviourmentioning
confidence: 99%
“…Nonetheless a recent study has demonstrated cleaning of large hosts (e.g. fish) by shrimp from temperate environments (Östlund-Nilsson et al, 2005;Jensen 2006). Most interestingly, we rarely observed crabs with their carapace covered by barnacles or any other fouling organism commonly found among rocks and mollusk shells at the study site.…”
Section: Association Between Betaeus Lilianae and Platyxanthus Crenulmentioning
confidence: 99%
“…Palaemon elegans is essentially omnivorous, feeding on foraminiferans, small invertebrates such as other crustaceans, molluscs, polychaetes, and insect larvae, but also on fish fry as well as algae and detritus (Kö hn & Gosselck 1989;Smaldon et al 1993;Jephson et al 2008;Persson et al 2008). In addition, the prawn was observed to feed on dermal ectoparasites of flatfish (Ö stlund-Nilsson et al 2005). On the other hand, the prawn may be a significant component of the food web as prey of predatory fishes, as suggested by Janas et al (2004) and Persson et al (2008).…”
Section: Introductionmentioning
confidence: 90%